Investigation of the keratinocyte transcriptome altered in high-glucose environment: An in-vitro model system for precision medicine. Issue 1 (January 2023) - Chen, Yang-Yi; Huang, Shu-Mei; Cheng, Yu-Wen; Yen, Meng-Chi; Hsu, Ya-Ling; Lan, Cheng-Che E.
Abstract: Background: Impaired wound healing is a serious diabetes complication compromising patients' quality of life. However, the pathogenesis of diabetic wounds (DWs) remains incompletely understood. Human epidermal keratinocyte (HEK) is the sentinel cell that initiates healing processes after the epidermal integrity has been disrupted. Objective: This study aimed to investigate the functional roles of HEKs in wound healing and to identify candidate genes, signaling pathways and molecular signatures contributing to the DWs. Methods: HEKs were cultured in normal or high-glucose environment, followed by scratch, to mimic the microenvironment of normal wounds and DWs. Subsequently, we performed RNA sequencing and systematically analyzed the expression profiles by bioinformatics approaches. Results: High-glucose environment altered the keratinocyte transcriptome responses to wounding. In experimental model of DWs, we found that TNF, CYP24A1, NR4A3 and GGT1 were key overexpressed genes in keratinocytes and were implicated in multiple cellular responses. Further analysis showed that wounding in high-glucose environment activated G-protein-coupled receptor (GPCR) signaling, cAMP response element-binding protein (CREB) signaling, and adrenomedullin signaling in keratinocytes, while dysregulated skin development and immune responses as compared to their counterpart in normal glucose settings. Conclusion: This simplified in-vitro model serves as a valuable tool to gain insights into the molecular basis of DWs and to facilitate establishment of personalized therapies in clinical practice Highlights: High-glucose environment altered the keratinocyte transcriptome responses to wounding. In high-glucose cultivated keratinocytes, TNF, CYP24A1, NR4A3 and GGT1 were key overexpressed genes after wounding. In high-glucose environment, wounding suppressed keratinocyte differentiation, while promoted myeloid leukocyte activation. Keratinocytes from different individuals demonstrated diverse cellular responses to wounding in high-glucose environment. The model is a valuable tool to explore the heterogeneity in the pathomechanism of diabetic wounds among individuals.